Changes in Self-Silencing From Adolescence to Emerging Adulthood and Associations With Relationship Quality and Coping With Relationship Stressors. (27th December 2018) - Shulman, Shmuel; Norona, Jerika C.; Scharf, Miri; Ziv, Ido; Welsh, Deborah P.
Abstract : Self-silencing is a tendency to suppress the expression of thoughts and opinions from a romantic partner due to the fear that this self-expression would lead to a dissolution of the relationship. The aim of the current study was to assess the longitudinal effects of self-silencing during adolescence and its change across time in the context of future romantic relationships at the age of 23. In the current study, the level of self-silencing was assessed among 144 adolescents (86 females) aged 16–18 years (mean age = 16.57 years). Seven years later at the age of 23, participants reported again on the level of self-silencing, the quality of their romantic relationships, and their ability to cope with romantic stressors. Employing regression analyses, results showed that self-silencing at age 16 predicted more concealment. In addition, changes in self-silencing over time explained the variance within future levels of concealment, partner support, relationship certainty, and posttraumatic growth. Embedded within a developmental framework, our results illuminate the importance of considering both initial levels of relational vulnerabilities and their change over time in future romantic relationships.